Internações hospitalares por doenças isquêmicas docoração, pelo SUS em Belo Horizonte: acesso, características e desfechos - Patricia Alves Evangelista (2005)
The Hospital Admission Centers (HAC) were set up as a tool to regulate patient access to hospital admission. However, many admissions occur directly via hospitals. The present dissertation, which is being presented by way of two scientific articles, looked into the existence of differences as well as into characteristics and outcomes of admissions made by the BH Unified Health System (SUS-BH), in 2002, according to type of access to hospital admission, direct or via HAC.The data were gathered from Authorizations for Hospital Admission (AIH), reports and requests for hospital beds in the City Department of Health. Admissions required for Acute Myocardial Infarction (AMI) and Coronary Insufficiency (CI) were included in the study. The first article compared, by means of cross-sectional analysis, the characteristics of admissions in relation to type of access. Out of 3705 admissions, 24.9% were made via HAC and 75.1% were by direct access. There were more direct Hospital admissions as compared with the ones made via HAC for patientsaged ³ 70 years (23.6% vs. 18.8%, p=0.001), with medical report of CAI (74.4% vs. 65.4%, p<0.001), at surgical clinic (9.1% vs. 5.4%, p<0.001), during weekends (20.9% vs. 17.6%, p=0.030) and for other invasive procedures related to ischemic diseases (8.8% vs. 5.0%, p<0.001). There were more admissions through the HAC, as compared with direct access, for patients residing outside BH (43.8% vs. 35.8%, p<0.001), at non-public hospitals (97.1% vs. 72.0%, p<0.001) and admitted to Intensive Care Unit (20.2% vs. 16.8%, p=0.020). The results also show discrepancies in types of access regarding costs and length of stay.The second article checked, by means of longitud inal study, if the means of access to hospitalization was associated with in- hospital death after adjusting the relevant factors. When there was more than one admission due to AMI or CI, only the last hospitalization was taken into account. Each hospital admission under analysis corresponded to a different patientThe results did not indicate any association between the means of access to hospital and risk of in-hospital death for the studied factors. The multivariate analysis showed that the risk of death was greater for: patients aged ³ 60 years, female sex, admission due to AMI, in Intensive Care Units (ICU), at public hospitals and in surgical specialization (clinic). Patients admitted to hospital due to AMI also showed greater risk of death if the admissions were made at weekends. The study demonstrated differences in the characteristics of admissions made by diverse types of access as well as and inequalities on the outcomes of healthcare. The results suggest the need of further investigations in order to assess healthcare provided at hospitals taking into account the influence of other factors such as structure of services, technology available, patient severity and co- morbidities and health care process in order to support new interventions and ensure greater equity and better quality of care.